Perception of the traditional Cerrado peoples about the implementation of the Chapada das Mesas National Park, Maranhão, Brazil - Silva, Maria Lindalva Alves da; Araújo, Maria de Fátima Veras; Conceição, Gonçalo Mendes da (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The Chapada das Mesas National Park was created in 2005 whit the objective of protecting the floristic, faunistic, diversity, endemic species, natural attributes, such as the presence of 400 river sources and morrarias carved by the process of natural weathering present in the region, known as Chapada das Mesas, located in the Cerrado phytogeographic domain, in the South of Maranhão, Brazil. Some aspect to be addressed when creating a conservation unit is the conflicts generated by the limitation of the exploration of natural resources by the residents of the place, where protected areas the land issue. In this sense, it is research had as objective investigate the participation of residents in the process of creating the Chapada das Mesas National Park. The research was descriptive, whit application of forms to 40 residents. Checked that 77.5% live in the Park. 75% did not participate in the project to implement the conservation unit and 50% were against. With the perspective of families living inside the conservation unit and with the elaboration of the Management Plan, the residents are expected to understand the importance of the National Park to preserve this ecosystem and to support its implementation.